APLIKASI BOOK CREATOR: PENGARUHNYA TERHADAP KEMAMPUAN MAHASISWA MENULIS TEKS PROSEDUR - Evi Handayani; Nurul Puspita; Nur Syamsiah (FKIP, Universitas Lakidende Unaaha, 2023)
This study investigates the influence of employing the Book Creator application on the development of students' writing abilities in composing procedural texts. Mastering the construction of procedural texts is a crucial skill for students, and Book Creator offers a potentially valuable tool to facilitate the clear and creative expression of their ideas. Employing a quasi-experimental design, this research examines the effect of Book Creator on the writing skills of eleventh-grade students at SMA N 1 Pasir Sakti. The target population comprised 302 students, from which two classes were selected through cluster random sampling: XI IPA 3 as the experimental group and XI IPS 3 as the control group, each consisting of 30 students. Pre-tests and post-tests served as the primary data collection instruments. Subsequent to normality and homogeneity testing of the data through SPSS v.24, an independent samples t-test was conducted. The results, with a significance level (p) of 0.003 (falling below the 0.05 alpha level), indicate that the utilization of the Book Creator application exerted a statistically significant influence on the enhancement of students' writing ability in procedural texts within SMAN 1 Pasir Sakti during the 2021/2022 academic year.